Review of the Asian Thaumastodinae (Coleoptera, Byrrhoidea, Limnichidae), with a phylogeny of the genera - Yoshitomi, Hiroyuki (European Journal of Taxonomy, 2019)
The Asian species of the subfamily Thaumastodinae Champion, 1924 are reviewed. Seven new species are described: Acontosceles borneensis sp. nov., Pseudeucinetus papuanus sp. nov., Mexico ogasawaraensis sp. nov., M. baliensis sp. nov., M. papuanus sp. nov., M. palauensis sp. nov. and M. borneensis sp. nov. The genus Babalimnichus Satô, 1994 is treated as a junior synonym of the genus Mexico Spilman, 1972, and three known species of the genus Babalimnichus are transferred to Mexico, viz. M. taiwanus (Satô, 1994) comb. nov., M. masamii (Satô, 1994) comb. nov. and M. splendens (Hernando & Ribera, 2003) comb. nov. Additional specimen data are shown, and new distributional records are as follows: Acontosceles chujoi Yoshitomi & Satô, 2005 from Vietnam; A. zetteli Pütz, 2008 from Laos; Pseudeucinetus javanicus Yoshitomi & Putra, 2010 from Lombok Island; Mexico taiwanus (Satô, 1994) comb. nov. from Lutao, Lanhsu and the Yonaguni-jima Islands; and M. masamii (Satô, 1994) comb. nov. from Kume-jima. A species list of the subfamily Thaumastodinae is given, with ZooBank LSIDs. The phylogenetic relationships of the thaumastodine genera are discussed.